Estudio de factibilidad para la implementación de una empresa productora de longaniza vegana a base de quinua con champiñones y su comercialización en la ciudad de Loja. - Herrera Ordoñez, Diana Maribel (2024)
Veganism in Ecuador is a trend that has been gaining traction in recent years. A "Feasibility Study for the Implementation of a Vegan Sausage Production Company based on Quinoa with Mushrooms and its Commercialization in the City of Loja" was conducted, considering substitute products in SUPERMAXI. The objectives include conducting a market study to determine demand, supply, and marketing plan; a technical study to understand the size, location, project engineering, and legal organization of the company; a financial study to assess investment and financing; and a financial evaluation to determine the feasibility of the project through financial indicators. The research employed an exploratory-descriptive approach with a mixed focus, utilizing surveys, interviews, and observations for data collection. The selected segment for the study was the population of Loja by families. The study revealed an unmet demand of 21,905.00 units per year, with a size of 14,940.00 packages of 250 grams of vegan sausage, located on Sucre Street between Catacocha and Lourdes. The company will be established as a Limited Liability Company, with an initial investment of $9,200.82, comprising self-financing of $3,680.33 and external financing of $5,520.49 with a 12% interest rate from Banco del Loja. The operating budget is $41,994.89 in the first year, with a unit cost of $2.81 and revenue of $49,386.00. Finally, the financial evaluation indicates a Net Present Value (VAN) of $12,981.94; an Internal Rate of Return (TIR) of 57.45%; a Benefit-Cost Ratio (RBC) of 1.15, yielding a profit of 0.15 cents for every dollar invested; a Payback Period (PRC) of 2 years, 7 months, and 17 days; the Sensitivity Analysis (AS) suggests that the project can withstand a 5.70% increase in costs and a 4.95% decrease in revenue. In conclusion, the project is feasible.